2018
DOI: 10.1177/0972150918794974
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Celebrity Credibility on Brand Attitude, Advertisement Attitude and Purchase Intention

Abstract: The celebrity credibility scale developed by Singh and Banerjee [Singh, R. P., & Banerjee, N. (2018). A study on exploring the factors influencing celebrity endorsement credibility. Global Business Review, 19(2), 494–509.] which is validated in the Indian context with the addition of some items based on Indian culture and psychometric properties is further tested. The scale items are earlier tested in general terms without any reference to a celebrity. For this study, four major two-wheeler brands in India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
2
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 76 publications
(92 reference statements)
16
100
2
21
Order By: Relevance
“…This study revealed the effects of source credibility such as source attractiveness, expertise, and trustworthiness influence positively consumer attitudes towards ad and brand subsequently purchase intention of cosmetic products. This finding corroborates with previous studies by Chekima & Chekima (2019), Schouten et al, (2020), Singh and Banarjee (2018), Thomas and Johnson (2017), and Muda et al, (2014). These results validated the source credibility from the perspective of social media influencer and its ability to exert a favorable outcome of consumers toward the ad.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This study revealed the effects of source credibility such as source attractiveness, expertise, and trustworthiness influence positively consumer attitudes towards ad and brand subsequently purchase intention of cosmetic products. This finding corroborates with previous studies by Chekima & Chekima (2019), Schouten et al, (2020), Singh and Banarjee (2018), Thomas and Johnson (2017), and Muda et al, (2014). These results validated the source credibility from the perspective of social media influencer and its ability to exert a favorable outcome of consumers toward the ad.…”
Section: Resultssupporting
confidence: 92%
“…To demote this from occurring, scholars of product differentiation (Schouten et al, 2020;Hannan et al, 1990) prompted that organizations may confront less rivalry by separating themselves from others through big name or influencer underwriting. Besides, it is powerful to utilize endorsers from the dependable source towards buyers which have a bothersome understanding of the item (Schouten et al, 2019;Singh and Banarjee, 2018;Thomas and Johnson, 2017;Daneshvary and Schwer, 2000). Consequently, the tenable source can neutralize these sentiments and have a positive result which is a greater message acceptance (Byrne et al, 2003).…”
Section: Underpinning Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[44]. In addition, previous studies proved that attitude toward the brand has a direct effect on purchase intention [18,[45][46][47][48]. In this way, these analyses suggest proposing the following hypothesis: on the environment in the whole process of purchase, use, and disposal [43].…”
Section: Hypothesis 12 Brand Credibility Positively Affects Purchase Intentionmentioning
confidence: 76%
“…Brand attitudes enhance purchase intentions among consumers as their motivation gets increased (Mackenzie & Spreng, 1992). The better the attitude towards the brand that is shown by consumers, the higher the level of consumers in purchasing intention (Jung & Seock, 2016;Sallam, MA, & Algammash, FA, 2016;Lee, E. B et al, 2017;Parks, JC , 2018;Yu, M. et al, 2018;de Villiers et al, 2018;Singh & Banerjee, 2018;Fitri, FR, 2018). The greater organizational responsibility will lead to more extreme emotions towards the organization followed by more extreme repurchase intentions with the direction of those who are dependent on customers' positive or negative experiences (Shank & Robinson, 2019).…”
Section: Introductionmentioning
confidence: 99%